First Results on the Mw=6.9 Samos Earthquake of 30 October 2020 - Papadimitriou, Panayotis; Kapetanidis, Vasilis; Karakonstantis, Andreas; Spingos, Ioannis; Kassaras, Ioannis; Sakkas, Vassilis; Kouskouna, Vasiliki; Karatzetzou, Anna; Pavlou, Kyriaki; Kaviris, George; Voulgaris, Nicholas (Bulletin of the Geological Society of Greece, 2020)
On 30 October 2020 11:51 UTC, a Mw=6.9 earthquake struck the offshore region north of Samos Island, Greece, in the Gulf of Ephesos/Kuşadasi, causing two fatalities and 19 minor injuries at Samos Island, as well as 115 casualties and over 1,030 injuries in Western Turkey. Preliminary results indicate that the mainshock occurred on a north-dipping normal fault, with a focal mechanism of 270º/50º/-81º. The selection of the fault plane is supported by evidence of uplift at western Samos and over 10 cm of subsidence at the northernmost edge of the central part of the island. The distribution of relocated hypocenters shows clustering of events, east of the mainshock’s epicenter, where most major aftershocks have occurred. To the west, a smaller group of aftershocks is observed, separated by a spatial gap in seismicity. The latter is likely related to the region of the fault plane where most of the co-seismic slip occurred, with Coulomb stress-transfer towards the western and eastern margins of the rupture triggering aftershock activity. The apparent complexity of the mainshock’s source time function, supported by preliminary results, could indicate the rupture of more than one structures. This could explain the relatively weak magnitude of the largest aftershock (Mw=5.0). The mainshock caused damage mainly to non-engineered constructions, i.e. old residential buildings, churches and monuments in Samos Island, and minor damage to the majority of the building stock of the island built according to the National Seismic Code. On the other hand, it caused severe damage at Izmir, especially to high-rise buildings. The mainshock also triggered a small tsunami that reached heights of over 1 m, mainly affecting the Turkish coast.